MICROSOFT ACCESS DATA PROCESSING AS A SUPPORTING INFORMATION DIRECTORATE OF SCHOOL EDUCATION IN UP FIRST - Effendi Veranon Simamora; Fitri Sjafrina, Skom, MMSI Fitri Sjafrina, Skom, MMSI (Jurnal Sistem Informasi, 2004)
Data space is one part of the Directorate of Advanced Education First (Dit. PLP), which is part of the Ministry of National Education (MONE). This part is pretty important role in terms of data services and information for each division-division in the Directorate. PLP.Writing is about the problems that arise in the handling of school data database, in terms of search data and preparing reports. The author proposes a database which abru to solve problems with Microsoft Access database.From the analysis, the authors tried to solve the problems occurring in the data room and especially for workers who handle data and information. The final part of the writing attached to the program as a supporter of the school principal data processing system.